Competing forces maintain the Hydra metaorganism. Issue 1 (September 2017) - Deines, Peter; Lachnit, Tim; Bosch, Thomas C. G.
Summary: Our conventional view of multicellular organisms often overlooks the fact that they are metaorganisms. They consist of a host, which is comprised of both a community of self‐replicating cells that can compete as well as cooperate and a community of associated microorganisms. This newly discovered complexity raises a profound challenge: How to maintain such a multicellular association that includes independently replicating units and even different genotypes? Here, we identify competing forces acting at the host tissue level, the host‐microbe interface, and within the microbial community as key factors to maintain the metaorganism Hydra . Maintenance of host tissue integrity, as well as proper regulation and management of the multiorganismic interactions are fundamental to organismal survival and health. Findings derived from the in vivo context of the Hydra model may provide one of the simplest possible systems to address questions on how a metaorganism is established and remains in balance over time.